The Mesoarchaean Akia terrane, West Greenland, revisited : new insights based on spatial integration of geophysics, field observation, geochemistry and geochronology - Steenfelt, Agnete; Hollis, Julie; Kirkland, Christopher L.; Sandrin, Alessandro; Gardiner, Nicholas J.; K. H. Olierook, Hugo; Szilas, Kristoffer; Waterton, Pedro; Yakymchuk, Chris (Precambrian Research, 2020)
NJG thanks Australian Research Council grant FL160100168 for financial support. The northern part of the North Atlantic Craton (NAC) in southern West Greenland comprises a large tract of exposed Meso-Neoarchaean continental crust, divided into the ca 3300–2900 Ma Akia and ca 2900–2500 Ma Tuno terranes. We combine aeromagnetic, stream sediment geochemical, new litho-chemical and zircon geochronological data with previously published data to re-evaluate the crustal architecture and evolution of the Akia terrane and its boundary towards the Tuno terrane. The previously recognised, but overlooked, Alanngua complex, situated between the Akia and Tuno terranes is bounded by aeromagnetic lineaments interpreted as Neoarchaean shear zones and has a distinct spectrum of Neoarchaean magmatic and metamorphic zircon ages that are rare in the Akia terrane. The Alanngua complex comprises components derived from both the Akia and Tuno terranes and is interpreted as a tectonic melange created during the Neoarchaean assembly of the NAC. Within the Akia terrane, the chemistry of orthogneiss samples indicate that a large percentage is too mafic to classify as TTG s.s., implying that not only partial melting of mafic crust, but also some yet unaddressed mantle involvement is necessary in their formation. Previous models for the generation of the ca. 3015–2990 Ma quartz-dioritic Finnefjeld and Taserssuaq complexes conflict with their geochemical variation. The complexes are spatially associated with strong aeromagnetic responses that are interpreted to reflect a large gabbro-diorite intrusion, and we propose that the protoliths of the Finnefjeld and Taserssuaq complexes are genetically linked to such intrusion. Formed at same time are carbonatite, high-Mg gabbro and tonalite-trondhjemite, and we propose that this wide spectrum of rocks could have formed by lithospheric and crustal melting in response to asthenospheric upwelling possibly in an extensional setting. Periods of extensive magmatism in the Akia terrane were previously ...